2010
DOI: 10.1590/s0104-56872010000400029
|View full text |Cite
|
Sign up to set email alerts
|

Contrastes e contrastes encobertos na produção da fala de crianças

Abstract: TEMA: análise acústica da fala. OBJETIVO: analisar acusticamente as "substituições" envolvendo o contraste entre /t/ e /k/ na fala de crianças em aquisição típica e desviante do contraste acima referido, a fim de identificar e quantificar a existência de contrastes encobertos. MÉTODO: foi elaborado um experimento de produção de fala que envolveu a repetição de palavras, que combinavam /t/ e /k/ com /a/ e /u/ na posição acentuada, por 9 crianças divididas em três grupos: crianças em processo de aquisição do con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 9 publications
2
9
0
6
Order By: Relevance
“…The observation of attempts of correct production of sounds, verified via spectrogram and, which were not previously identified by auditory perceptual analysis, has already been reported and confirmed by many studies of the area 1,5,6,10,11,[15][16][17][18] . A research 5 that also investigated the voicing contrast of the stop phones found that a group of children with speech and difficulty in stabilizing the feature [+ voice] did not distinguish acoustically the voiced x voiceless contrast.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The observation of attempts of correct production of sounds, verified via spectrogram and, which were not previously identified by auditory perceptual analysis, has already been reported and confirmed by many studies of the area 1,5,6,10,11,[15][16][17][18] . A research 5 that also investigated the voicing contrast of the stop phones found that a group of children with speech and difficulty in stabilizing the feature [+ voice] did not distinguish acoustically the voiced x voiceless contrast.…”
Section: Discussionsupporting
confidence: 65%
“…That fact seems to be confirmed in another theoretical perspective through the covert contrast [15][16][17][18][19] . For the discrimination of voicing contrast, it was observed in this research that only one of the children had a low performance in the SVDT, with a percentage of less than 50% of correct answers.…”
Section: Figure 4 -Errors Total By Minimal Pairs In the Stop Voicinmentioning
confidence: 60%
See 1 more Smart Citation
“…Speech data from all individuals were collected and submitted to acoustic analysis. variables present in the production of fricatives, because, in this way, the production of all individuals would have the same target (9)(10)(11)(12)(13)(14)(15)(16) . The only exception was the variable word position, which was a target of this study.…”
Section: Thismentioning
confidence: 99%
“…Phonetically speaking, the lack of adaptation to the production might occur due to children's problems involving acquisition and/or manipulation of acoustic cues (SCOBBIE et al, 2000;BERTI;MARINO, 2011). Children may resort to phonetically inappropriate cues for a given language (that is, inappropriate use of acoustic cues) and/or may use appropriate phonetic cues for the given language, but with an unexpected magnitude: with insufficient or exaggerated values, characterizing the so-called covert contrasts (SCOBBIE et al, 2000).…”
Section: Introductionmentioning
confidence: 99%